Novel Reverse Phase Liquid Chromatography Method for Accurate Determination of Vasopressin in Pharmaceutical Products - Chimaji Aher; Nagarajan Kayalvizhi; N. Puvaneswari; Muthukalingan Krishnan; Aruni Wilson Santhosh Kumar; Neelamegam Rameshkumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
A simple, gradient, reproducible, and selective RPHPLC technique was developed and validated in this work to quantify assay of drug substance and drug product.Separation was achieved with Agilent HPLC with C18 column, with mobile phase containing 0.1% Orthophosphoric acid in water and Acetonitrile. 50 µlof sample was injected in mobile phase at flow rate of 1 ml per minute at column oven of 25°C. Detection done at 220 nm by using UV detector. The developed method was validated for specificity, system suitability, Linearity, Precision, Accuracy and Robustness. The developed method was found to be acceptable in terms of specificity and system suitability.The excellentlinearity was found between 4 to 60 µg/mL with correlation coefficient(R) of 0.9994. The low %RSD values for both RT and peak area indicate excellent system precision. The average assay was found to be 101.4%, STDEV of 0.769, and %RSD of 0.76% demonstrating the method's precision. Across all spiking levels (80%, 100%, and 120%,) the results showed minimal variation, indicating the method'ssuitability for accurate determination. Parameters including column oven temperature, and flow rate did not hinder the RT, theoretical plates, asymmetry and area indicating robust method.The RP-HPLC method developed for vasopressin was validated and applied to the analysis of three different API lots and found to be acceptable. The measured vasopressin content for both formulations (19.76 IU/ml for BRAND-1 and 19.95 IU/ml for BRAND-2) closely matched their labelled amounts of 20.0 IU/ml. These results demonstrate that the developed method is robust and reliable for the quantitative analysis of drug substance and marketed vasopressin formulations, ensuring consistent and accurate drug content determination.